Ultrasound-derived muscle assessment system for older adults: a promising muscle mass estimation tool. (29th December 2022) - Tang, Xinyi; Huang, Songya; Huang, Li; Feng, Ziyan; Wang, Ziyao; Yue, Jirong; Qiu, Li
Abstract: Background: Quantitative assessment of muscle mass is a critical step in sarcopenia disease management. Expanding upon the use of ultrasound in foetal growth assessment, we established and validated an ultrasound-derived muscle assessment system for older adults at a risk of sarcopenia. Methods: A total of 669 older adults were recruited in three cohorts in this cross-sectional study. In cohort 1( n = 103), the most valuable sites for skeletal muscle mass index (SMI) estimation were located among 11 ultrasound scanning sites. An ultrasound-derived SMI estimating algorithm based on muscle thickness (MT) was obtained in the modelling group composed of cohorts 1 and 2 ( n = 309). The reliability of the muscle mass estimation equation and the validity of the obtained cut-off values were verified in cohort 3 ( n = 257), which was selected as the verification group. Results: In the modelling group, the cut-off values of ultrasound-derived e-SMI for low SMI were 7.13 kg/m 2 for men and 5.81 kg/m 2 for women. In the verification group, the intraclass correlation between e-SMI and SMI was 0.885. The sensitivity of the e-SMI in detecting low SMI was 93.6% for men and 89.7% for women, and the negative predictive value was 94.9% for men and 94.7% for women. Combined with the handgrip strength and gait speed, the e-SMI had an overall diagnostic sensitivity of 92.7% and a specificity of 91.0% for sarcopenia. Conclusion: The ultrasound-derived muscle assessment system can be a promising muscle mass estimation tool and a potential disease classification tool.